On the international transmission of technology shocks - Enders, Zeno; Müller, Gernot J. (Journal of international economics, 2009)
Using vector autoregressions on U.S. time series and an aggregate of industrialized countries, we find that technology shocks appreciate the terms of trade and lower the trade balance; they induce an ‘S’-shaped cross-correlation function for both variables (the S-curve). In calibrating a prototypical international business cycle model under complete and incomplete financial markets, we find two distinct sets of parameter values. While both model specifications deliver the S-curve, the underlying transmission mechanism of technology shocks is fundamentally different. Most importantly, only in the incomplete markets economy the terms of trade appreciate and thus amplify the relative wealth effects of technology shocks—as suggested by the evidence.